In Memoriam Geoffrey Burnstock: Creator of Purinergic Signaling. Issue 1 (25th June 2020) - Verkhratsky, Alexei; Zimmermann, Herbert; Abbracchio, Maria P; Illes, Peter; DiVirgilio, Francesco
Abstract: Geoff Burnstock (1929–2020) discovered purinergic signaling in a fastidious research that started in early 1960 and culminated in a concept of purinergic nerves in 1972. Subsequently, Geoff developed the concept of purinergic transmission and demonstrated ATP storage, release, and degradation in the context of cotransmission, which was another fundamental concept developed by him. Purinergic transmission contributes to the most fundamental physiological functions such as sensory transduction, regulation of heart rate, smooth muscle contraction, bile secretion, endocrine regulation, immune responses, as well as to various pathophysiological conditions, including inflammation, cancer, neuropathic pain, diabetes, and kidney failure.